Beberapa Sifat Biskuit dari Campuran Tepung Beras Kaya Protein dan Tepung Kacang Hijau Untuk Makanan Tambahan Bayi Usia Di Bawah Dua Tahun - E.Y. Purwani; B.A.S. Santosa; K.D. Meihira; D.S. Damardjati (agriTECH, 1996)
The objectives of this study were: (1) to evaluate some characteristics of biscuit made from high protein rice flour and mungbean flour mixture and (2) to evaluate the calori and protein consumption of the biscuit as suplement food among young children under two years old. Amylolitic enzyme was used to hydrolize the gelatinized starch in the rice flour into water soluble maltose and dextrin. Filtration and drying were done to separate the unhydrolized solid. The solid would contain higher protein, which consequently called High Protein Rice Flour (HPRF). The HPRF was mixed with mungbean flour at ratio of 6:4, 7:3 and 8:2, respectively. The mixed flour was then processed into biscuit.Result indicated that the biscuit contained 1.49-to-1.57% of ash, 9.37-to-9.88 of fat and 9.31-to-9.96 of protein, respectively. Water absorption capacity, oil absorbtion capacity and bulk density value were 1.71-to-1.81 g/g, 1.68-to-1.79 g/g and 0.48-to0.50 g/m1 respectively. Mixing HPRF and mungbean flour at ratio of 6:4 resulted in a superior quality, therefore, this product was then Oven to the young children. The biscuit contributed 17-to-23% of calori and 15-to-20% of protein for young children. It was alsc observed that biscuit made of HPRF and mungbean flour mixture was potential for contributing calori and protein requirement, especially for low income group.